Is There a Bridge Between Systemic Lupus Erythematosus and Thymomas? - Xie QIBING; Yin HENG; Tao YE; Chen XI; Yin GENG (Archives of Rheumatology, 2013)
In this report, we describe a 21-year-old male patient who developed a type C thymoma (undifferentiated carcinoma) after five years of stabilized systemic lupus erythematosus (SLE) activity. The patient remained stable even after chemoradiotherapy for the thymoma, and at the one-year follow-up, treatment had no effect on the progression of the SLE. Previous data regarding the coexistence of SLE and thymomas suggested that interaction occurs between these two diseases through some implicit mechanisms. However, we believe that no interaction takes place between two diseases, based on our experience and related literature data.